Mouth Corset Vibration Berbasis Sinyal Frekuensi Penggetar Sebagai Alat Terapi Pada Penderita Pasca Stroke Ringan - Setiahawati Setiahawati; Monica Merry Febriyana; Zulfandi Zulfandi; Zahra Ayu Damayanti; Irnin Agustina Dwi Astuti (UNIVERSITAS INDRAPRASTA PGRI, 2021)
Stroke is a disorder that attacks the functional organs of the brain in the form of nerve paralysis (neurological deficit) due to the cessation of blood supply to the brain. One of the treatments that can be done is by doing facial massage in the form of vibration, since this treatment can mechanically stimulate important internal organs and can physiologically can stimulate autonomic (unconscious) nervous system in internal organs through external actions. Using latest innovations, we present an equipment we like to call